Ethnic differences in blood pressure monitoring and control in south east London - Schofield, Peter (Royal College of General Practitioners, 2011)
BACKGROUND: High blood pressure is the single most important risk factor worldwide for the development of cardiovascular disease, and has been shown to affect some ethnic minority groups disproportionately. AIM: To explore ethnic inequalities in blood pressure monitoring and control. METHOD: Data from Lambeth DataNet was used, based on case records from GP practices in one inner-city London borough. Blood pressure monitoring and control was compared using Quality and Outcomes Framework (QOF) targets for patients with: diabetes, coronary heart disease, stroke, hypertension, and chronic kidney disease. The study controlled for age, sex, social deprivation, and clustering within GP practices. RESULTS: A total of 16 613 patients met the study criteria, with 5962 categorised as black/black British. Blood pressure monitoring was similar across ethnic groups and as good, if not better, for black patients compared to white. However, marked ethnic inequalities in blood pressure control were found, with black patients significantly less likely to achieve QOF targets than their white counterparts (odds ratio [OR] 0.73; 95% confidence interval [CI] = 0.64 to 0.82). Further inequalities were revealed in blood pressure control within disease groups and ethnic subgroups. In particular, blood pressure control was poor in African patients with diabetes (OR 0.63; 95% CI = 0.50 to 0.79) and Caribbean patients with coronary heart disease (OR 0.53; 95% CI = 0.37 to 0.77) when compared with white patients. DISCUSSION: While black patients with chronic conditions are equally likely to have their blood pressure monitored, their blood pressure control is consistently poorer than that of their white counterparts. This may have important implications for cardiovascular risk management in black patients.